Clinical Response of Convalescent Plasma Therapy in COVID-19 Patients in Dr. Saiful Anwar General Hospital - Niniek Budiarti Burhan; Herwindo Pudjo Brahmantyo; Djoko Heri Hermanto; Putu Moda Arsana (Jurnal Kedokteran Brawijaya, 2021)
The use of convalescent plasma has been beneficial for more than a century to treat various infections.Â  The lack of effective treatment currently available for COVID-19 has reemerged the use of convalescent plasma as a potential therapeutic option. This is an observational descriptive study in 13 COVID-19 patient who got convalescent Plasma. Consist of 11 (84%) male patient, 2 (16%) female patient. Divided into two groups based on severity, and outcome. 38% patient included in severe disesase and 62% patient in critically Ill condition. 30% patient who got convalescent plasma deceased, and 70% had a resolve condition.